Influences of High-Speed Train Speed on Tunnel Aerodynamic Pressures - Jianming Du; Qian Fang; Jun Wang; Gan Wang (Applied Sciences, 2021)
To comprehensively investigate the characteristics of aerodynamic pressures on a tunnel caused by the whole tunnel passage of a high-speed train at different speeds, we conduct a series of three-dimensional numerical simulations. Based on the field test results obtained by other researchers, the input parameters of our numerical simulation are determined. The process of a high-speed train travelling through a railway tunnel is divided into three stages according to the spatial relationship between the train and tunnel. Stage I: before train nose enters the entrance; Stage II: while the train body runs inside the tunnel; Stage III: after the train tail leaves the exit. The influences of high-speed train speed on the tunnel aerodynamic pressures of these three stages are systematically investigated. The results show that the maximum peak pressure value decreases with increasing distance from the entrance and increases with increasing train speed in Stage I. There is an approximately linear relationship between the three types of maximum peak pressure (positive peak, negative peak, and peak-to-peak pressures) and the power of the train speed in Stage II. These three types of maximum peak pressure values of the points near tunnel portals increase with increasing train speed in Stage III. Moreover, these three types of maximum peak pressure in the tunnel’s middle section at different train speeds are more complex than those near the tunnel portals, and there is one or more turning points due to the superimposed effects of different pressure waves.